Ретроспективний аналіз становлення і розвитку дитячої періодичної преси в Україні (з кінця ХІХ ст. до 1991 року) - Нагорна, О.М. (Інститут літератури ім. Т.Г. Шевченка НАН України, 2009)
В статье отображены основные этапы развития детской периодической прессы на Украине. Исследование охватывает период с конца ХІХ века до годов независимости государства. Материал представляет периодические издания в четко установленном хронологическом порядке. Рассмотрены наиболее популярные журналы и газеты, сделан анализ их направленности, аудитории и основных рубрик. In the article the basic stages of development of children's periodics in Ukraine are displayed. The research covers the period from the end of ХІХ century about years of independence of the state. The material represents the periodics in the precisely established chronological order. The most popular magazines and newspapers are considered, the analysis of their orientation, audience and basic headings is made.